Analysis of Time Spent to Carry Out Age-Based Simultaneous and Sequential Simulated Fire Evacuation in Indoor Gymnasium - Jae-Chun Ahn; Ha-Sung Kong (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study aims to analyze time spent to carry out age-based simultaneous and sequential simulated fire evacuation in indoor gymnasium. The result shows: First, it took 334.8 seconds to carry out simultaneous evacuation for RSET of all occupants, which demonstrated bottleneck phenomenon in the steps along the aisle of audience seats and entrance of fire door. Second, it turned out that it took a total of 352 seconds to carry out sequential evacuation which set the 1st priority on children followed by the elderly and grown-ups in the space of 10 seconds. Third, it was revealed that it took a total of 325.1 seconds to carry out sequential evacuation setting 1st priority on children followed by the elderly and grown-ups in the space of 20 seconds. Finally, when the interval was set at 30 seconds, it took a total of 313.6 seconds to complete sequential evacuation with the other conditions being made identical to the above one. The result shows that fire evacuation setting 1st priority on occupants slow to move and time interval at 30 seconds is the most effective in saving evacuation time.